MYC2-Activated TRICHOME BIREFRINGENCE-LIKE37 Acetylates Cell Walls and Enhances Herbivore Resistance. Issue 2 (30th July 2020) - Sun, Aiqing; Yu, Bo; Zhang, Qian; Peng, Yu; Yang, Jing; Sun, Yonghua; Qin, Ping; Jia, Tao; Smeekens, Sjef; Teng, Sheng
Abstract : A polysaccharide acetyltransferase family gene plays a pivotal role in cell wall structure and is activated by MYC2-dependent jasmonate signaling, enhancing herbivore defense in Arabidopsis. Abstract: O -Acetylation of polysaccharides predominantly modifies plant cell walls by changing the physicochemical properties and, consequently, the structure and function of the cell wall. Expression regulation and specific function of cell wall-acetylating enzymes remain to be fully understood. In this report, we cloned a previously identified stunted growth mutant named sucrose uncoupled1 ( sun1 ) in Arabidopsis ( Arabidopsis thaliana ). SUN1 encodes a member of the TRICHOME BIREFRINGEN-LIKE family, AtTBL37 . AtTBL37 is highly expressed in fast-growing plant tissues and encodes a Golgi apparatus-localized protein that regulates secondary cell wall thickening and acetylation. In sun1, jasmonate signaling and expression of downstream chemical defense genes, including VEGETATIVE STORAGE PROTEIN1 and BRANCHED-CHAIN AMINOTRANSFERASE4, are increased but, unexpectedly, sun1 is more susceptible to insect feeding. The central transcription factor in jasmonate signaling, MYC2, binds to and induces AtTBL37 expression. MYC2 also promotes the expression of many other TBLs . Moreover, MYC activity enhances cell wall acetylation. Overexpression of AtTBL37 in the myc2-2 background reduces herbivore feeding. Our study highlights the role of O- acetylation in controlling plant cell wall properties, plant development, and herbivore defense.